Perlindungan Hukum Terhadap Anak Sebagai Perantara Narkotika (Study Putusan No.14/Pid.Sus Anak.2015/PN.Dps) - Rezky Ayu Saraswati; I Nyoman Sujana; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2021)
The rise of drug trafficking involving children as narcotics couriers is a problem that needs serious attention from both the government, law enforcement and the community. Children who commit crimes must continue to obtain legal protection in the best interests of the child. Child protection is contained in Law number 11 of 2012 concerning the juvenile justice system, where at the moment children can become narcotics abuse even as narcotics brokers with the rampant abuse of narcotics for all circles both in Indonesia and in the international world. The formulation of the problem raised is how is the basis for judges' consideration in imposing criminal sanctions on children as intermediaries for narcotics? And what is the legal protection of children as an intermediary for narcotics? The problems to be discussed will be examined based on normative perspectives and the legislative approach to the decisions of the Denpasar District Court No. 14 / Pid.Sus Anak / 2015 / PN. Dps, that the judge considers that the accused child has committed narcotics crimes by being charged Law number 35 of 2009 concerning narcotics, which can be sentenced to a minimum of 5 years and a maximum of 20 years and can be subject to fines. Legal protection for children is carried out by judges by imposing criminal training on employment in a generation of Indonesian foundations, solely so that children can carry out their activities as usual when they return to the community and do not disturb their psychic rights and can increase their skills in children. The child does not return to committing a crime.